Exploring Islamic Educational Counseling as an Alternative Solution for Student Moral Development in the Modern Era at MAS Plus Al-Ulum - Widya, Fazira; Habiburrozaq, Habiburrozaq; Jihan, Khairunnisa; Neng , Neng Nurcahayati Sinulingga (Adabiyah Islamic Journal, 2025)
Technological developments and cultural globalization have significantly impacted students' lives, particularly in their moral and spiritual aspects. Phenomena such as ethical decline, identity crises, and deviant behavior pose serious challenges to education. This study aims to explore the application of Islamic educational counseling as an alternative solution for student moral development at MAS Plus Al-Ulum, an Islamic high school that integrates general and religious curricula. The research approach used was a qualitative case study, with data collection techniques through observation, in-depth interviews, and documentation. The results show that Islamic counseling at this school is reflective, spiritual, and personal, instilling the values of honesty, trustworthiness, patience, and responsibility through a contextual approach. The strategy used involves collaboration between guidance counselors and Islamic education teachers, and is supported by an moral mentoring program, daily religious activities, and Islamic leadership training. The study also found indicators of changes in student character, such as increased discipline, social awareness, and spiritual awareness. However, challenges remain, such as limited resources, the influence of the digital environment, and the minimal role of the family. This study concludes that Islamic educational counseling is an effective approach to developing students' morals in the modern era, with the caveat that systemic support from schools, families, and communities is necessary. Keywords: Islamic Education Counseling; Student Moral Development; Modern Era